2013
DOI: 10.4103/1319-2442.109582
|View full text |Cite
|
Sign up to set email alerts
|

Value of sonography in the diagnosis of mild, moderate and severe vesicoureteral reflux in children

Abstract: This study was conducted to determine the positive predictive value (PPV) of gray scale sonography in the diagnosis of mild, moderate and severe vesicoureteral reflux (VUR). This cross-sectional descriptive analytic study was conducted in the University Clinic of Isfahan University of Medical Sciences in 2008. The study was performed on children aged two to 12 years; female children with febrile urinary tract infection (UTI) and clinical suspicion of VUR and males with history of UTI and VUR who attended follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In another investigation, Adibi and colleagues demonstrated the sensitivity, speci city; NPV and PPV of US in diagnosis of VUR were 70.9%, 51.4%, 69.6% and 52.9% respectively. They suggested that US is a sensitive but not speci c method in diagnosis of VUR (18).…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation, Adibi and colleagues demonstrated the sensitivity, speci city; NPV and PPV of US in diagnosis of VUR were 70.9%, 51.4%, 69.6% and 52.9% respectively. They suggested that US is a sensitive but not speci c method in diagnosis of VUR (18).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography now plays a valuable role in the diagnosis of VUR, however the most definite diagnosis of VUR is made with VCUG or radionuclide cystography (RNC), sonography may be used as the first step in evaluation for VUR, especially in high-grade VUR [23]. Recently Duran and his colleagues proposed the use of Voiding Ultrasonography (VUS) as US examination using US contrast agent (microbubbles) as part of initial diagnosis of reflux [24].…”
Section: Discussionmentioning
confidence: 99%
“…The most significant factor among these was the grade of ultrasonography findings. In previous retrospective reports, abnormal ultrasonography findings such as dilation of the ureter and pyelectasis were considered useful for predicting VUR , whereas other retrospective and prospective reports indicated that abdominal ultrasonography is of little benefit for diagnosing VUR. Although the utility of ultrasonography findings in predicting VUR is controversial, the ultrasonography findings were extremely useful and important for predicting VUR in this retrospective study and all of the prior reports demonstrated the high specificity of ultrasonography for predicting high‐grade VUR.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study was a retrospective study performed by investigating all medical records, and VUR grades were determined by each paediatrician who performed VCG, although we checked most of the images taken at the time of VCG, there was a limitation concerning the diagnostic accuracy. Moreover, retrospective or prospective studies of children with primary VUR all differ in the demographics of the population studied. These studies had a variety of designs with differences in inclusion and exclusion criteria as well as in the numbers of patients, patient age, healthcare delivery systems, sociocultural characteristics and race and ethnic variables that can influence the obtained results, reducing the ability to generalise the findings to all populations.…”
Section: Discussionmentioning
confidence: 99%